2020
DOI: 10.1002/cbic.202000187
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Alkylation Cascades: Recent Advances and Future Opportunities for Late‐Stage Functionalization

Abstract: This Concept article describes the latest developments in the emerging area of late-stage biocatalytic alkylation. Central to these developments is the ability to efficiently prepare Sadenosyl methionine (SAM) cofactor analogues and couple this with enzymatic alkyl transfer. Recent developments in the enzymatic synthesis of SAM cofactor analogues are summarized first, followed by their application as alkyl transfer agents catalyzed by methyltransferases (MTases). Second, innovative methods to regenerate SAM co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 76 publications
0
31
0
6
Order By: Relevance
“…The “magic methyl effect” refers to the ability of an appropriately placed methyl group to dramatically alter the biological properties of a compound [1] . This makes selective alkylation of molecules highly desirable [2] . Bioalkylations are important because of the exquisite chemo‐, regio‐ and stereospecificity achievable using enzymes [2, 3] .…”
Section: Figurementioning
confidence: 99%
“…The “magic methyl effect” refers to the ability of an appropriately placed methyl group to dramatically alter the biological properties of a compound [1] . This makes selective alkylation of molecules highly desirable [2] . Bioalkylations are important because of the exquisite chemo‐, regio‐ and stereospecificity achievable using enzymes [2, 3] .…”
Section: Figurementioning
confidence: 99%
“…Several elegant strategies for enzymatic synthesis of NSA have been developed [19–21] . These approaches still depend on the laboratory synthesis of methionine analogs as NSA precursors that limits their application [11, 18, 22] . Liao and Seebeck have recently shown that SAM can be enzymatically synthesized and recycled (Figure 1 B).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Commonly used chemical methylation agents such as methyl iodide or dimethyl sulfate are often carcinogenic, mutagenic, and harmful to the environment. The biocatalytic application of MTs, also using SAM analogues, [8][9][10][11][12] are promising starting points for sustainable methods. 13,14 While SAM analogues allowing to transfer larger alkyl chains have been widely employed for product diversification, [15][16][17][18][19][20][21][22][23][24][25] the variation of the nucleobase has become a new focus, especially regarding the long-term goal to make bioorthogonal systems available.…”
Section: Introductionmentioning
confidence: 99%